Early-high-strength micro-expansion shrinkage-free grouting material and preparation method thereof

Through the preparation method of multi-scale nanomaterials and hydration dynamic regulation, the problems of insufficient strength, shrinkage cracking and poor durability in the early stage of traditional grouting materials are solved, and the early stage high-strength, micro-expansion, no shrinkage and excellent durability of high-performance grouting materials are achieved. It is suitable for high-performance projects such as nuclear power containment shells and large-span bridge support.

CN120483648AActive Publication Date: 2025-08-15CCCC FIRST ENG & CONSTR RES INST CO LTD +2

Patent Information

Application Number
CN202510769129.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-08-15
Estimated Expiration
2045-06-10

AI Technical Summary

Technical Problem

Traditional grouting materials have shortcomings in early strength, cracking caused by volume shrinkage, poor durability and poor thermal stability, which are difficult to meet the needs of high-performance engineering. Existing improvement methods such as adding expansion agents, shrinkage agents or fibers have certain effects, but they have problems such as unstable expansion, high cost, complex process or poor dispersion of nanomaterials.

Method used

The preparation method of multi-scale nanomaterial collaboration, grading optimization and hydration kinetic regulation is adopted. Through the composite of silicate cement, sulfoaluminate cement and nanosilicon dioxide, combined with the precise mixing of functionalized nanocalcium carbonate, nanographene oxide and quartz sand aggregate, a grout material with early high strength, slightly expanded, no shrinkage, and excellent durability.

Benefits of technology

High-performance grouting materials with a compressive strength of 1h ≥32MPa, a compressive strength of 28d ≥102MPa, a shrinkage of 28d ≤0.015%, and a thermal expansion coefficient of ≤1.2×10-6/℃ are achieved. They are suitable for harsh environments such as nuclear power containment shells and large span bridge support, improving construction efficiency and structural safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120483648A_ABST
    Figure CN120483648A_ABST
Patent Text Reader

Abstract

The invention discloses an early-strength micro-expansion shrinkage-free grouting material and a preparation method thereof, and belongs to the technical field of new materials. The high-performance grouting material is prepared through cooperation of multi-scale nano materials, grading optimization and hydration dynamic regulation. The preparation method comprises the following steps: pretreatment of gelling powder, preparation of dispersed sol, preparation of a nano expansion regulating agent, preparation of a nano filling system and a nano enhanced mixing process. The main performance indexes are as follows: the 1h compressive strength is greater than or equal to 32MPa, the 1d compressive strength is greater than or equal to 62MPa, and the 28d compressive strength is greater than or equal to 102MPa; the 3h expansion rate is 0.6-0.95%, and the 28d shrinkage rate is less than or equal to 0.015% The initial fluidity is greater than or equal to 305mm, and the retention value in 30 minutes is greater than or equal to 265 The freeze-thaw mass loss is less than or equal to 3.8%, the chloride ion diffusion coefficient is less than or equal to 1.8 * 10 <-12 > m < 2 > / s, and the thermal expansion coefficient is less than or equal to 1.2 * The grouting material has the advantages of early strength, high strength, micro-expansion, no shrinkage, high fluidity, excellent durability, low thermal expansion and the like, and is suitable for engineering scenes with high-performance requirements, such as nuclear power containment and large-span bridge supports.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to an early high-strength micro-expansion non-shrinkage grouting material and a preparation method thereof. Background Art

[0002] Grouting material is an important building material and plays an irreplaceable role in modern engineering construction. It is usually composed of multiple components such as cement, aggregate, admixtures and additives. It has good fluidity and adhesion, can fill in narrow spaces and quickly solidify to form a high-strength structural layer. Grouting materials are widely used in buildings, bridges, tunnels, water conservancy projects and other fields, especially in equipment foundation reinforcement, structural repair, waterproofing and plugging, and prestressed pipe grouting. It plays a key role. With the continuous advancement of engineering technology, the requirements for the performance of grouting materials are increasing, especially the demand for early strength, shrinkage performance and durability is becoming more and more urgent. However, traditional grouting materials have some significant defects in practical applications, which limit their application in high-performance engineering.

[0003] A major problem with traditional grouting materials is their insufficient early strength. In many engineering scenarios that require rapid construction, such as emergency repair projects, urgent reinforcement, or prefabricated component installation, the early strength of the grouting material directly determines the construction progress and structural safety. However, traditional grouting materials usually require a long curing time to reach the design strength, which not only prolongs the construction period but may also increase construction costs. In addition, shrinkage cracking is another prominent problem with traditional grouting materials. During the hardening process, due to water evaporation and chemical reactions, the grouting material will shrink in volume, leading to the formation of cracks. These cracks not only affect the appearance, but also weaken the bearing capacity and durability of the structure, and even pose a safety hazard. In addition, traditional grouting materials also have shortcomings in durability, such as poor freeze-thaw resistance and poor impermeability. These problems are particularly evident in harsh environments.

[0004] In order to overcome the above-mentioned defects of traditional grouting materials, researchers have proposed a variety of improvement methods and technologies. Among them, adding expansion agents is a common means to solve the shrinkage problem. Expansion agents can produce micro-expansion during the hardening process of the grouting material, offset part of the shrinkage stress, and thus reduce the risk of cracking. However, the effect of expansion agents is often unstable, greatly affected by environmental conditions and material batches, and difficult to accurately control. In addition, excessive use of expansion agents may cause the strength of the grouting material to decrease, affecting its mechanical properties. Another method is to add shrinkage reducing agents, which can reduce the shrinkage rate of the grouting material and improve its volume stability, but its cost is high and may have a negative impact on fluidity and other properties. In addition, the application of reinforcing fibers has also been widely studied. Fibers can improve the crack resistance and toughness of grouting materials. However, the dispersion of fibers and their bonding with the matrix are key issues. The preparation process is complex and the cost is high, which limits its large-scale application.

[0005] In recent years, the application of nanomaterials in grouting materials has attracted widespread attention. Due to their unique physical and chemical properties, nanomaterials can significantly improve the microstructure and performance of grouting materials. For example, nanosilica can promote cement hydration and increase early strength; nanocalcium carbonate can fill micropores and improve density; and nanographene oxide can enhance mechanical properties and durability. However, the application of nanomaterials still faces challenges, such as the easy agglomeration of nanoparticles, insufficient compatibility with the matrix, and complex preparation processes, which have limited their widespread use in grouting materials.

[0006] Conventional grouting materials typically utilize simple mechanical stirring to uniformly mix the components. However, this method struggles to achieve uniform dispersion of nanomaterials, hindering their full performance. Furthermore, conventional processes also have shortcomings in controlling fluidity and workability, making them difficult to meet the demands of high-performance grouting materials. Therefore, developing a novel preparation method that achieves uniform dispersion while optimizing performance is crucial.

[0007] In summary, traditional grouting materials have deficiencies in early strength, shrinkage performance, and durability. While existing improvement methods have shown some effectiveness, they still face challenges such as stability and cost. This invention overcomes these challenges through technological innovation, providing a new solution for the development and application of high-performance grouting materials, with significant engineering value and market potential. Summary of the Invention

[0008] 1. Problems to be solved

[0009] To address the problems of existing grouting materials, such as insufficient early strength, cracking due to volume shrinkage, poor durability, and poor thermal stability, the present invention aims to provide an early high-strength, micro-expansion, non-shrinkage grouting material and its preparation method to meet the needs of high-performance engineering scenarios such as nuclear power containment and long-span bridge bearings. Specifically, traditional grouting materials have difficulty achieving a compressive strength of ≥32MPa within 1 hour in rapid construction scenarios, and the 28d strength is usually less than 100MPa, limiting construction efficiency and structural safety. Volume shrinkage during the hardening process (28d shrinkage rate is often ≥0.05%) can easily cause cracks and weaken structural durability. Freeze-thaw resistance and corrosion resistance are insufficient (chloride ion diffusion coefficient is often ≥5×10 -12 m 2 / s, acid erosion strength retention rate ≤80%), which makes it difficult to cope with harsh environments; in addition, the thermal expansion coefficient of traditional grouting materials is high (usually ≥2×10 -6 / °C), which is prone to thermal stress damage in environments with large temperature differences. Existing improvement methods, such as adding expansion agents, shrinkage reducers, or fibers, have some effectiveness, but they suffer from unstable expansion, high costs, complex processes, and poor dispersion of nanomaterials, making it difficult to fully meet high-performance requirements.

[0010] The present invention solves the above problems through innovative material formula and preparation process, and develops a kind of high-strength early-stage material (1h compressive strength ≥32MPa, 1d ≥62MPa, 28d ≥102MPa), slight expansion without shrinkage (3h expansion rate 0.6-0.95%, 28d shrinkage rate ≤0.015%), high fluidity (initial fluidity ≥305mm), excellent durability (freeze-thaw resistance mass loss ≤3.8%, chloride ion diffusion coefficient ≤1.8×10 -12 m 2 / s) and low thermal expansion (thermal expansion coefficient ≤ 1.2×10 -6 / ℃) grouting materials provide reliable material solutions for high-performance projects.

[0011] 2. Technical solution

[0012] To solve the above problems, the present invention adopts the following technical solutions.

[0013] A method for preparing an early-stage high-strength micro-expansion non-shrinkage grouting material comprises the following steps: a. pre-treatment of a gelled powder: mixing silicate cement, sulfoaluminate cement and nano-silicon dioxide, and then ball milling at a speed of 500-800 rpm for 60-120 minutes under inert atmosphere protection to obtain a composite gelled powder with a particle size of 0.5-2 μm; b. preparation of a dispersed sol: dispersing nano-titanium dioxide, functionalized nano-calcium carbonate and cellulose ether in deionized water under ultrasonic conditions for 30-60 minutes to form a stable dispersed sol; c. preparation of a nano-expansion regulating agent: mixing magnesium oxide micropowder, calcium sulfoaluminate with nano-graphene oxide and deionized water; Mix to form a nano-expansion regulator; d. Preparation of nano-filling system: quartz sand aggregate, silica fume and slag powder are selected, and the nano-filling system is obtained by ball milling and homogenization; e. Nano-enhanced mixing process: the composite gelled powder of step a and the nano-filling system of step d are dispersed and mixed in a high-speed disperser at 150-200 rpm for 2-3 minutes, then the nano-expansion regulator of step c is added and the dispersion mixing is continued for 1-2 minutes, and then the dispersed sol of step b is added while increasing the stirring speed to 250-350 rpm and mixing for 5-8 minutes; finally, 5-10 times the mass of the dispersed and dissolved energy storage material is added, and finally a shear homogenization treatment is performed to obtain the product.

[0014] Preferably, the mass ratio of Portland cement, sulfoaluminate cement, and nano-silica in step a is (40-60): (8-15): (0.5-2); the particle size of the nano-silica in step a is 10-30 nm. For Portland cement (PC), basic properties include: strength grade: typically 42.5 or higher, indicating a 28-day compressive strength of 42.5 MPa or higher. Particle size: median particle size of approximately 11.74 µm, specific surface area of approximately 356 m 2 / kg. Chemical composition: The main components are CaO (62.8%), SiO2 (21.7%), Al2O3 (5.45%), Fe2O3 (3.41%), etc. For sulfoaluminate cement (CSA), basic properties: Strength grade: usually 42.5R, indicating rapid hardening characteristics, 28d compressive strength reaches or exceeds 42.5MPa. Particle size: The median particle size is about 13.56µm. Chemical composition: The main components are CaO (39.7%), Al2O3 (27.3%), SiO2 (13.8%), SO3 (10.9%), etc., with high sulfate and aluminate content. Synergistic strengthening mechanism of ternary composite cementitious system: (1) Portland cement: dominates the later strength development, generates CSH gel and Ca(OH)2, with a specific surface area of 356m 2 / kg to ensure full hydration; sulfoaluminate cement: quickly generates ettringite (AFt) skeleton, 3h expansion rate of 0.5-1.2%, 1d strength contribution ≥50%; nano-silica: pozzolanic reaction consumes Ca(OH)2 to generate CSH gel, filling pores (specific surface area ≥200m 2 / g). (2) Particle size matching and microstructure optimization: PC / CSA particle size synergy: PC (D50 = 11.74µm) and CSA (D50 = 13.56µm) form a continuous gradation, increasing the bulk density by 12-15% and reducing water demand. Nano-SiO2 effect: 10-30nm particle size enhances performance through the following mechanisms: Nucleation effect: acts as a CSH heterogeneous nucleation site, accelerating the hydration reaction rate by 3-5 times; Micro-filling effect: fills 10-100nm pores and reduces the total porosity by ≥30%; Chemical activation: surface silanol groups (Si-OH) react with Ca 2+ The reaction generates CSH, and the strength after 1 day is increased by 20-35%. (3) Hydration kinetics control: Early stage (0-12h): CSA rapidly hydrates to generate AFt, and nano-SiO2 promotes the hydrolysis of C3S in PC. The strength after 10 hours can reach 40-50% of the strength after 28 days. Mid-term stage (12h-7d): PC dominates the formation of CSH gel, and nano-SiO2 continuously consumes Ca(OH)2. The Ca(OH)2 content is reduced by 60-80% after 28 days. Long-term stage (7d-28d): AFt and CSH synergistically form an interlocking structure with a compressive strength of ≥100MPa and a shrinkage of ≤0.02%. Scientific basis for key parameters: CSA:PC ratio (8-15:40-60): Ensure that the ratio of AFt to CSH generated is 1:2-1:3, which not only ensures early strength but also avoids excessive expansion. Nano-SiO2 content (0.5-2%): Exceeding 3% results in a 30-50% decrease in fluidity due to agglomeration. This mix balances activity and workability. Particle size control (10-30nm): 40nm particles provide optimal filling, but 10-30nm particles can achieve similar results with improved dispersibility through surface modification. This mix achieves a high-performance grouting system with a 1-day compressive strength ≥60MPa, a 28-day strength ≥100MPa, and a volume change rate ≤0.02% through the synergistic effect of particle size optimization, hydration stage control, and nano-enhancement technology.

[0015] Preferably, the mass ratio of nano-titanium dioxide, functionalized nano-calcium carbonate, cellulose ether (CAS No. 9004-32-4) and deionized water in step b is (0.1-0.8): (0.05-0.3): (0.02-0.1): (15-22); the particle size of the nano-titanium dioxide in step b is 5-15 nm; and the ultrasonic conditions in step b are as follows: power 200-400 W, frequency 40 kHz.

[0016] Preferably, the preparation method of the functionalized nano-calcium carbonate in step b is as follows: a calcium chloride solution with a concentration of 0.5-1.5 mol / L and a sodium carbonate solution with a concentration of 0.5-1.5 mol / L are rapidly mixed at a molar ratio of 1: (2-4) at 20-30°C, the stirring speed is controlled at 300-500 rpm, and the reaction time is 30-60 min to generate a nano-calcium carbonate suspension with a particle size controlled at 20-50 nm; 0.05-0.2 times the mass of the silane coupling agent KH- 570 or KH-550, and adjust the pH value of the solution to 8.0-9.0, and use ultrasonic dispersion treatment with a power of 200-400W and a frequency of 40kHz for 30-60min to form a modified suspension; the modified suspension is centrifuged to remove unreacted impurities, wherein the centrifugal speed is 5000-8000rpm, wherein the centrifugal time is 10-20min, and washed with deionized water 3-5 times, and then dried in a vacuum drying oven at 60-80℃ for 6-12h to obtain functionalized nano-calcium carbonate. The functionalized nano-calcium carbonate preparation method achieves performance optimization through the following mechanisms: (1) Nano-calcium carbonate synthesis stage: chemical precipitation control: using a molar ratio of CaCl2 to Na2CO3 of 1: (2-4), suppressing excessive particle growth (Ostwald ripening mechanism) through a carbonate excess strategy, combined with a stirring speed of 300-500rpm to form a uniform shear force field, promoting the nucleation rate to be greater than the growth rate, and achieving precise control of the particle size of 20-50nm. Low temperature reaction kinetics: Slow down the ion diffusion rate at 20-30℃ to avoid local supersaturation leading to agglomeration, and promote the transformation of amorphous precursor to calcite crystal form. (2) Surface functionalization modification: Silane coupling agent bonding mechanism: KH-570 (containing methacryloyloxy) or KH-550 (containing amino) hydrolyzes to silanol (Si-OH) at pH 8.0-9.0, and dehydrates and condenses with the hydroxyl (-OH) on the surface of nano-calcium carbonate to form Si-O-Ca covalent bonds, thus constructing an organic-inorganic interface layer. Ultrasonic cavitation effect: 40kHz ultrasound generates microjets and cavitation bubble rupture, destroying the van der Waals force between particles and promoting the directional adsorption of silane molecules to achieve monolayer coating (coverage rate > 90%). (3) Post-processing process optimization: Centrifugal purification: 5000-8000rpm high-speed centrifugation selectively separates unreacted ions (such as Cl - 、Na + ) and large-sized aggregates (>100nm), ensuring the monodispersity of the product (PDI <0.2). Vacuum drying to prevent agglomeration: 60-80℃ low temperature vacuum conditions inhibit secondary agglomeration caused by capillary force, retaining the nano-scale pore structure (BET specific surface area 40-60m 2 / g). (4) The role of functionalized nano-calcium carbonate in grouting materials: Nucleating agent: Surface silane groups provide high-energy active sites to accelerate heterogeneous nucleation of CSH gel, and the 1d compressive strength is increased by ≥15%; Micro-expansion control: KH-550 amino groups and Ca 2+ Coordination retards the formation rate of AFt (ettringite), stabilizing the 3-hour expansion rate at 0.5-1.2%. Interface enhancement: Organic functional groups form hydrogen bonds with the polymer matrix (such as polycarboxylate superplasticizer), achieving interfacial bond strength ≥8 MPa. Key parameters are scientifically based on a molar ratio of 1:(2-4): Excess carbonate ions inhibit the dissolution and recrystallization of CaCO3 through the common ion effect, limiting grain size (Langmuir adsorption model). Ultrasonic power of 200-400W: At an energy density of 0.5-1.0 W / mL, the cavitation threshold breaks through the particle aggregation energy barrier (≈10 kT), achieving efficient dispersion. This process achieves controlled size and precise surface functionalization of nano-calcium carbonate through chemical-mechanical synergy, providing an optimized microstructural control method for early-stage high-strength grouting materials.

[0017] Preferably, in step c, the mass ratios of magnesium oxide powder (CAS No. 1309-48-4), calcium sulfoaluminate (CAS No. 960375-09-1), nanographene oxide and deionized water are (1.5-4): (0.3-1.2): (0.1-0.5): (6-10). The parameters of nanographene oxide are as follows: CAS No. 7782-42-5. For functionalized GO materials with a sheet thickness of 1-3nm, a 0.1-0.5% addition can increase the flexural strength by 30-50% (through crack bridging and interface enhancement). MgO:CSA ratio (1.5-4: 0.3-1.2): ensure that the expansion pressure gradient is ≤0.5MPa / day to avoid structural damage. GO dosage (0.1-0.5%): when it exceeds 0.5%, agglomeration occurs due to van der Waals forces, and the specific surface area increases from 263m 2 / g dropped to 150m 2 / g. Particle size matching: MgO (5-20μm) and GO (1-3nm) form a multi-scale filling, reducing porosity by 40%. This ratio, through the combination of spatiotemporal control of the expansion phase and nano-enhancement technology, achieves a high-performance grouting system with a 1-day compressive strength ≥60MPa and a 28-day shrinkage ≤0.03%, suitable for harsh environments such as nuclear power containment.

[0018] Preferably, the mass ratio of quartz sand aggregate, silica fume and slag powder in step d is (100-150): (2-8): (1-5); the parameters of ball milling in step d are as follows: speed 400-500 r / min, time 12-18 h; the parameters of homogenization in step d are as follows: pressure: 40-60 MPa, number of cycles: 3-5 times.

[0019] The synergistic effect of mass ratio (quartz sand aggregate: silica fume: slag powder = 100-150: 2-8: 1-5): Quartz sand aggregate: provides skeleton support, optimizes gradation (0.05-1.2mm continuous distribution) and increases bulk density to 75-80%. Silica fume: nano-scale filling (specific surface area ≥ 20000m 2 / kg) reacts with volcanic ash, and the strength is increased by 15-25% in 1 day. Slag powder: Potential activity is stimulated (alkaline environment releases Ca 2+ ), contributing 10-15% to the 28-day strength, and reducing the chloride ion diffusion coefficient by 50%. Micro-control of the ball milling process (400-500 rpm, 12-18 hours): The shear force generated by ball milling deagglomerates the slag glass, increasing the release of active SiO2 and Al2O3 by 2-3 times. Macro-optimization of high-pressure homogenization (40-60 MPa, 3-5 cycles): Pressures of 40-60 MPa eliminate bubbles >100 μm, reduce porosity from 8-10% to 3-5%, and improve impermeability by 2-3 grades (P ≥ P12). 3-5 cycles destroy silica fume agglomerates (from 10 μm to <1 μm), increase the thickness of the quartz sand-cementitious interface transition zone (ITZ) from 20 μm to 5 μm, and increase the interfacial bond strength from 5 MPa to 8 MPa. Temperature control <40℃: prevent prehydration caused by thermal activation, ensure fluidity retention value ≥90%, and extend the construction time window to 60-90min. Multi-scale structural synergy: Nanoscale: silica fume fills 10-100nm pores, and the density of CSH gel nucleation sites increases by 10 3 / cm 3 At the micron level, ball-milled quartz sand creates a concave-convex surface, increasing mechanical bite by 30%. At the macro level, high-pressure homogenization reduces defect size from 500μm to less than 50μm, improving fracture toughness by 50%. This process achieves a high-performance grouting system with a 1d compressive strength of ≥65MPa and a 28d shrinkage of ≤0.02%, through precise control of gradation matching, activity stimulation, and defect elimination. It is suitable for demanding applications such as grouting in long-span bridge bearings.

[0020] Preferably, in step d, the mass ratio of the composite gelled powder, the dispersed sol, the nano-swelling control agent, and the nano-filling system is (80-100): (8-12): (2-4): (1-2); the parameters of the shear homogenization treatment in step d are as follows: rotation speed 400-500 rpm, time 30-60 s. In step d, the composite gel powder (80-100 parts), dispersed sol (8-12 parts), nano-expansion regulator (2-4 parts) and nano-filling system (1-2 parts) achieve performance optimization through the following synergistic mechanism: the composite gel powder provides the main strength skeleton as the matrix (1d compressive strength ≥ 60MPa), the dispersed sol ensures the uniform dispersion of nanoparticles through electrostatic stabilization (Zeta potential ≥ 30mV), the nano-expansion regulator (magnesium oxide / calcium sulfoaluminate composite system) accurately controls the 3h expansion rate (0.5-1.2%), and the nano-filling system (silica fume / GO composite) reduces the porosity to ≤3% through size gradient filling (10nm-1μm). High-speed shear homogenization treatment at 400-500rpm for 30-60s is carried out, and the instantaneous shear rate is ≥10 3 s -1 The hydrodynamic effect breaks up the nanoaggregates (size is reduced from 500nm to <100nm) and forms chemical bonds at the interface (Ca-O-Si bond energy ≥530kJ / mol), ultimately achieving a performance balance of slurry fluidity ≥300mm and 28d shrinkage ≤0.02%.

[0021] Preferably, the preparation method of the energy storage material in step d is as follows: paraffin wax (CAS number 8002-74-2) and sodium sulfate decahydrate (CAS number 7727-73-3) are selected in a mass ratio of 1:(3-5) as the phase change material; polymethyl methacrylate (CAS number 9011-14-7) is dissolved in acetone at 20-40 times its mass to prepare a shell material solution; the phase change material is dispersed in deionized water at 30-50 times its mass, and then polyvinyl alcohol at 5-10 times the mass of the phase change material is added. Under high-speed stirring at 1200-1500 rpm, 2-3 times the mass of the shell material solution of the phase change material is added dropwise to form an oil-in-water emulsion, the temperature is raised to 70-80°C, the reaction is carried out for 4-6 hours to complete the shell polymerization, and then the microcapsules are separated by centrifugation at 8000 rpm for 10 minutes, and the microcapsules are washed alternately with ethanol and deionized water three times, and vacuum dried at 40°C for 24 hours to obtain the energy storage material.

[0022] Composite phase change material optimization: Paraffin wax provides high latent heat (180-220 J / g) but low thermal conductivity (0.2 W / m·K). Sodium sulfate decahydrate compensates for this thermal conductivity (0.5 W / m·K) by releasing / absorbing crystalline water (latent heat 250-300 J / g). The composite achieves a latent heat of ≥200 J / g and a 50% improvement in cycling stability (capacity retention >90% after 500 thermal cycles). Microcapsule shell construction: A low viscosity (50-100 cP) in the shell material solution facilitates uniform shell formation. The 2-5 μm shell thickness is adjustable via the solvent concentration, and a glass transition temperature of 105°C ensures high-temperature stability. Emulsification stability of polyvinyl alcohol: A 5-10% addition of polyvinyl alcohol forms an oil-in-water emulsion with an HLB value of 16-18, reducing the interfacial tension to <10 mN / m, and controlling the droplet size to 50-200 μm (laser particle size analysis). Interfacial Polymerization Control: In-situ polymerization at 70-80°C: Thermal decomposition of the initiator generates free radicals, which polymerize the methyl methacrylate monomer at the droplet interface. Reaction Kinetics: Ensure monomer conversion >95% within 4-6 hours and shell crosslink density ≥80% (determined by the swelling method).

[0023] An early high-strength slightly expansive non-shrinkage grouting material is obtained by the above-mentioned preparation method.

[0024] 3. Beneficial effects

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention achieves excellent properties of grouting materials such as early strength, high strength, micro expansion and no shrinkage through the synergistic effect of multi-scale nanomaterials, gradation optimization and hydration dynamics control. The following is an in-depth analysis of the mechanism of its beneficial effects from three dimensions: material ratio, reaction mechanism and microstructure: (1) Early strength and high strength mechanism: Nanomaterial synergistic effect, nano-silica (10-30nm) consumes Ca(OH)2 through volcanic ash reaction to generate CSH gel, and the 1d strength is increased by 20-35%. Its specific surface area is ≥200m 2 / g characteristics, can fill 10-100nm pores, reduce the total porosity ≥30%. Functionalized nano-calcium carbonate surface silane groups provide high-energy active sites, accelerate CSH heterogeneous nucleation, and increase the 1d compressive strength by ≥15%. KH-550 amino and Ca 2+Coordination delays the formation rate of ettringite, stabilizing the expansion rate at 0.5-1.2% for 3 hours. Hydration kinetics regulation: Temporal and spatial regulation of the formation of the sulfoaluminate cement / portland cement composite system: rapid formation of the ettringite skeleton in the early stage (0-12 hours), CSH gel dominates in the middle stage (12 hours-7 days), and an interlocking structure is formed in the late stage (7-28 days). The 1-hour strength reaches 40-50% of the 28-day strength, and the 28-day compressive strength is ≥102MPa. (2) Micro-expansion without shrinkage mechanism: The expansion source is synergistically controlled, and the magnesium oxide / calcium sulfoaluminate composite system produces gradient expansion: magnesium oxide hydrates to form Mg(OH)2 (volume expansion 2.1 times), and calcium sulfoaluminate forms ettringite (volume expansion 1.5 times). The expansion pressure gradient between the two is ≤0.5MPa / day. Nanographene oxide (sheet thickness 1-3nm) inhibits shrinkage by crack bridging, and a 0.1-0.5% addition increases the flexural strength by 30-50%. Shrinkage compensation technology: Energy storage material microcapsules (paraffin / sodium sulfate composite phase change material) release latent heat (≥200J / g) when the temperature difference changes, controlling the thermal expansion coefficient to ≤1.2×10 -6 / ℃. 28d drying shrinkage is ≤0.015%, which is 70% lower than that of traditional grouting materials. (3) Durability improvement principle: Microstructure optimization, high-pressure homogenization process (40-60MPa) reduces the porosity from 8-10% to 3-5%, the thickness of the quartz sand-cementitious interface transition zone (ITZ) is reduced from 20μm to 5μm, and the interface bonding strength is increased from 5MPa to 8MPa. The nanofilling system (silica fume / GO composite) forms a 10nm-1μm size gradient filling, and the chloride ion diffusion coefficient is ≤1.8×10 -12 m 2 / s, which is 64% lower than the national standard. Enhanced chemical stability: The organic functional groups of functionalized nano-calcium carbonate form a hydrogen bond network with the polycarboxylate water reducer, and the acid erosion strength retention rate is ≥88%. The mass loss after 50 freeze-thaw cycles is ≤3.8%, which is better than the requirements of GB / T50448 standard. (4) Contribution of process innovation: The nano-enhanced mixing process adopts 400-500rpm high-speed shearing, and the instantaneous shear rate is ≥10 3 s -1 Nanoagglomerates are broken down (reducing size from 500nm to <100nm), and a zeta potential of ≥30mV ensures dispersion stability. This process achieves a slurry fluidity of ≥305mm while maintaining a 28-day shrinkage of ≤0.015%, resolving the fluidity-volume stability trade-off in traditional processes. Through this innovative mechanism, the present invention achieves breakthrough performance in harsh environments such as nuclear power containment, achieving a 1-hour compressive strength of ≥32MPa and a 28-day strength of ≥102MPa. This represents a 60% increase in early-stage strength and a three-fold improvement in volume stability compared to similar products (such as CN102351492A). BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a physical picture of the gelled powder prepared in Example 1.

[0028] Figure 2 This is a physical picture of the nano expansion agent prepared in Example 1.

[0029] Figure 3 This is a transmission electron microscope image of the energy storage material prepared in Example 1. DETAILED DESCRIPTION

[0030] The present invention is described in detail below through specific examples. However, the use and purpose of these exemplary embodiments are merely illustrative of the present invention and are not intended to limit the actual scope of protection of the present invention in any form, nor are they intended to limit the scope of protection of the present invention to these examples. For parameter ranges not mentioned, intermediate values are selected. In addition, for mass percentages or weight percentages not explicitly stated or mentioned, they generally refer to the final concentration after addition.

[0031] Example 1

[0032] Cementitious powder pretreatment: 40 g of Portland cement (PC, strength grade 42.5, median particle size 11.74 µm), 8 g of sulfoaluminate cement (CSA, strength grade 42.5R, median particle size 13.56 µm), and 0.5 g of nano-silica (particle size 10 nm) were mixed under an inert atmosphere (nitrogen) and ball-milled at 500 rpm for 60 min to obtain a composite cementitious powder with a particle size of 0.5-2 µm.

[0033] Preparation of dispersed sol: Take 0.1g of nano-titanium dioxide (particle size 5nm), 0.05g of functionalized nano-calcium carbonate (particle size 20nm), 0.02g of cellulose ether (CAS No. 9004-32-4), and 15g of deionized water, and disperse them under 200W, 40kHz ultrasonic conditions for 30 minutes to form a stable dispersed sol. Preparation of functionalized nano-calcium carbonate: Mix 0.5mol / L calcium chloride solution and 0.5mol / L sodium carbonate solution in a molar ratio of 1:2, stir at 20℃ and 300rpm for 30 minutes to generate a 20nm nano-calcium carbonate suspension; add 0.05 times the mass of silane coupling agent KH-570, adjust the pH to 8.0, and ultrasonically disperse at 200W and 40kHz for 30 minutes; centrifuge at 5000rpm for 10 minutes to remove impurities, wash 3 times with deionized water, and vacuum dry at 60℃ for 6 hours. The prepared gelled powder is as follows Figure 1 shown.

[0034] Preparation of nano-swelling regulator: 1.5 g of magnesium oxide powder (CAS No. 1309-48-4), 0.3 g of calcium sulfoaluminate (CAS No. 960375-09-1), 0.1 g of nano-graphene oxide (GO, CAS No. 7782-42-5, sheet thickness 1-3 nm), and 6 g of deionized water were mixed to form a nano-swelling regulator, such as Figure 2 shown.

[0035] Preparation of nanofilling system: Take 100g quartz sand aggregate (particle size 0.05-1.2mm), 2g silica fume (specific surface area ≥20000m 2 / kg), 1g of slag powder, ball milled at 400rpm for 12h, and then homogenized at 40MPa high pressure for 3 times to prepare the nanofilling system.

[0036] Nano-enhanced mixing process: Take 80g of composite gelled powder and 1g of nano-filling system, disperse and mix them in a high-speed disperser at 150rpm for 2min; add 2g of nano-swelling regulator and continue to disperse and mix for 1min; add 8g of dispersing sol, increase the stirring speed to 250rpm, and mix for 5min; add 40g of energy storage material (5 times the mass of the dispersed solution), shear and homogenize at 400rpm for 30s to obtain the product. Figure 3 Preparation: Paraffin wax (CAS No. 8002-74-2) and sodium sulfate decahydrate (CAS No. 7727-73-3, mass ratio 1:3) were used as phase change materials; polymethyl methacrylate (PMMA, CAS No. 9011-14-7) was dissolved in 20 times acetone to prepare a shell material solution; the phase change material was dispersed in 30 times deionized water, 5 times polyvinyl alcohol was added, and the mixture was stirred at 1200 rpm. 2 times the shell material solution was added dropwise, and the mixture was reacted at 70°C for 4 hours, centrifuged at 8000 rpm for 10 minutes, and washed alternately with ethanol and deionized water three times, and dried in a vacuum at 40°C for 24 hours.

[0037] Example 2-18

[0038] Examples 2-18 refer to the process flow and experimental methods of Example 1, but some parameters (such as the mass of each component and process conditions) are adjusted according to the endpoint values and intermediate values of the claim range, as shown in Table 1.

[0039] Comparative Example 1

[0040] Different from Example 1, functionalized nano-calcium carbonate was not used. In step b, an equal amount of ordinary nano-calcium carbonate (particle size 20 nm, not modified with silane coupling agent) was used instead, while other conditions remained unchanged.

[0041] Comparative Example 2

[0042] Different from Example 1, functionalized nano-calcium carbonate was not added in step b, but was replaced by an equal amount of deionized water, while other conditions remained unchanged.

[0043] Comparative Example 3

[0044] Different from Example 1, no energy storage material is added in step e, and other conditions remain unchanged.

[0045] Comparative Example 4

[0046] Different from Example 1, in step e, only paraffin wax (without sodium sulfate decahydrate) is used as the energy storage material, the mass is still 40 g, and other conditions remain unchanged.

[0047] Comparative Example 5

[0048] Different from Example 5, functionalized nano-calcium carbonate was not used. In step b, an equal amount of ordinary nano-calcium carbonate (particle size 30 nm, not modified with silane coupling agent) was used instead, while other conditions remained unchanged.

[0049] Comparative Example 6

[0050] Different from Example 5, functionalized nano-calcium carbonate was not added in step b, but was replaced by an equal amount of deionized water, while keeping other conditions unchanged.

[0051] Comparative Example 7

[0052] Different from Example 5, no energy storage material is added in step e, and other conditions remain unchanged.

[0053] Comparative Example 8

[0054] Different from Example 5, in step e, only paraffin wax (without sodium sulfate decahydrate) is used as the energy storage material, the mass is still 60 g, and other conditions remain unchanged.

[0055] Comparative Example 9

[0056] Different from Example 10, functionalized nano-calcium carbonate was not used. In step b, an equal amount of ordinary nano-calcium carbonate (particle size 50 nm, not modified with silane coupling agent) was used instead, and other conditions remained unchanged.

[0057] Comparative Example 10

[0058] Different from Example 10, functionalized nano-calcium carbonate was not added in step b, but was replaced by an equal amount of deionized water, while keeping other conditions unchanged.

[0059] Comparative Example 11

[0060] Different from Example 10, no energy storage material is added in step e, and other conditions remain unchanged.

[0061] Comparative Example 12

[0062] Different from Example 10, in step e, only paraffin wax (without sodium sulfate decahydrate) is used as the energy storage material, the mass is still 80 g, and other conditions remain unchanged.

[0063] Comparative Example 13

[0064] Different from Example 1, no nano-swelling regulator was used, and an equal amount of deionized water was used instead in step e, while other conditions remained unchanged.

[0065] Comparative Example 14

[0066] Different from Example 5, no nano-swelling regulator was used, and an equal amount of deionized water was used instead in step e, while other conditions remained unchanged.

[0067] Comparative Example 15

[0068] Different from Example 10, no nano-swelling regulator was used, and an equal amount of deionized water was used instead in step e, while other conditions remained unchanged.

[0069] Comparative Example 16

[0070] Different from Example 1, the nano-enhanced mixing process in step e was not performed. The composite gelled powder, dispersed sol, nano-swelling regulator, nano-filling system and energy storage material were simply mixed in the same mass ratio, stirred evenly and then allowed to stand, keeping other conditions unchanged.

[0071] The following is a summary of the process parameters and ratios of Examples 1-18 and Comparative Examples 1-16, in grams (g). The process conditions cover the endpoints and intermediate values of all parameters in the claims.

[0072] Table 1 Summary of process parameters for Examples 1-18

[0073]

[0074]

[0075] Table 2 Summary of process parameters for comparative examples 1-16

[0076]

[0077]

[0078]

[0079] Design examples: Examples 1-18 cover the endpoints (minimum and maximum) and intermediate values of the parameters in each step of the claims, ensuring comprehensive verification of the feasibility of the formulation and process conditions. The parameters of steps a, b, c, d, and e were adjusted proportionally, and the mass of the energy storage material was designed to be 5-10 times the dispersed and dissolved mass.

[0080] Comparative Examples: Comparative Examples 1, 5, and 9: Verify the role of functionalized nano-calcium carbonate by replacing it with conventional nano-calcium carbonate to examine the effects of surface modification on nucleation and interfacial strength. Comparative Examples 2, 6, and 10: Remove functionalized nano-calcium carbonate to verify its necessity for micro-expansion control and strength. Comparative Examples 3, 7, and 11: Remove the energy storage material to verify its contribution to thermal regulation and long-term stability. Comparative Examples 4, 8, and 12: Use only paraffin as the energy storage material to verify the synergistic effect of paraffin and sodium sulfate decahydrate.

[0081] Comparative Examples 13-15: Eliminating the nano-expansion modulator to verify its effect on micro-expansion and volume stability. Comparative Example 16: Omitting the nano-enhanced mixing process to verify the importance of high-speed shear homogenization for dispersion and interfacial bonding. Synergistic Enhancement Verification: By omitting key components or processes in the comparative examples, the synergistic contributions of functionalized nano-calcium carbonate (nucleation, interfacial enhancement), energy storage materials (thermal regulation), nano-expansion modulators (volume stability), and nano-enhanced mixing processes (uniform dispersion, chemical bonding) to early strength, micro-expansion, and shrinkage-free properties are highlighted.

[0082] Physical Property Testing: The grouts prepared in Examples 1-18 and Comparative Examples 1-16 were tested for fluidity and setting time using the following methods: Fluidity: Initial fluidity and 30-minute retention were measured using a truncated cone fluidity meter in accordance with GB / T 50448-2015. The water-to-material ratio was 0.14, and the ambient temperature was 20±2°C. Setting Time: Initial and final setting times were measured using a Vicat instrument to control the construction window.

[0083] Mechanical properties test: Compressive strength and flexural strength were tested using the following methods: Compressive strength: According to JC / T986-2018, the press loading rate was 2.4 kN / s, and the compressive strength was measured at 1 hour, 3 hours, 1 day, and 28 days. Flexural strength: The flexural strength was measured at 28 days using the three-point bending method.

[0084] Volume stability test: Test vertical expansion rate and thermal expansion coefficient as follows: Vertical expansion rate: Dial gauge method, measure 3h expansion rate and 28d shrinkage rate, refer to GB / T50082-2009. Thermal expansion coefficient: Thermomechanical analyzer (TMA) measures the thermal expansion coefficient in the range of 20-60℃.

[0085] Durability testing: Freeze-thaw resistance and corrosion resistance were tested using the following methods: Freeze-thaw resistance: 50 cycles of rapid freezing were performed, and mass loss and strength loss were measured. Corrosion resistance: 90 days of immersion in a 5% NaCl solution were used to measure the chloride ion diffusion coefficient; 28 days of corrosion in a 10% H2SO4 solution were used to measure the strength retention rate.

[0086] Microstructure Analysis: Hydration products and pore structure were analyzed using the following methods: Hydration products: XRD analysis was used to determine the ratio of ettringite (AFt) to CSH gel, and thermogravimetric analysis (TGA) was used to determine the 28dCa(OH)2 content. Pore structure: Mercury intrusion porosimetry (MIP) was used to determine the total porosity and pore size distribution, and to observe the dispersion of the nanomaterial.

[0087] The following are the test results of Examples 1-18 and Comparative Examples 1-16, which are summarized in Table 3.

[0088] Table 3 Performance test results of Examples 1-18 and Comparative Examples 1-16

[0089]

[0090]

[0091]

[0092]

[0093]

[0094]

[0095]

[0096] Result Analysis

[0097] Example 1-18: Physical properties: initial fluidity ≥305mm, 30min retention value ≥265mm, initial setting time ≤40min, final setting time ≤220min, meeting construction requirements. Mechanical properties: 1h compressive strength ≥32MPa, 3h ≥52MPa, 1d ≥62MPa, 28d ≥102MPa, flexural strength ≥15.5MPa, indicating excellent early strength and long-term strength. Volume stability: 3h expansion rate 0.6-0.95%, 28d shrinkage rate ≤0.015%, thermal expansion coefficient ≤1.2×10 -6 / ℃, achieving the goal of micro expansion and no shrinkage. Durability: freeze-thaw resistance mass loss ≤3.8%, strength loss ≤15%, chloride ion diffusion coefficient ≤1.8×10 -12 m 2 / s, acid erosion strength retention rate ≥88%, excellent durability. Microstructure: total porosity ≤2.8%, Ca(OH)2 content ≤2.5%, indicating that the nanomaterial effectively fills the pores and optimizes the hydration products.

[0098] Comparative Examples 1-16: Comparative Examples 1, 5, and 9 (non-functionalized nano-calcium carbonate): initial fluidity decreased to 287-290 mm, 1-day compressive strength decreased to 54-55 MPa, 28-day shrinkage increased to 0.030-0.032%, and total porosity increased to 4.0-4.1%. The absence of functionalized nano-calcium carbonate reduced the nucleation effect and interfacial bonding strength, resulting in decreased strength and volume stability. Comparative Examples 2, 6, and 10 (complete removal of nano-calcium carbonate): performance further deteriorated, 1-day compressive strength decreased to 51-53 MPa, 28-day shrinkage increased to 0.035-0.037%, and chloride ion diffusion coefficient increased to 2.6-2.9×10 -12 m 2 / s, indicating that nano calcium carbonate is crucial for micro expansion control and durability. Comparative Examples 3, 7, and 11 (without energy storage material): The thermal expansion coefficient increased to 1.65-1.7×10 -6 / ℃, the freeze-thaw resistance loss increased to 20-21%, indicating the contribution of energy storage materials to thermal regulation and durability. Comparative Examples 4, 8, and 12 (energy storage materials using only paraffin wax): the thermal expansion coefficient increased to 1.7-1.75×10 -6 / °C, acid etch strength retention dropped to 80-81%, indicating that the synergistic effect of paraffin wax and sodium sulfate decahydrate improves thermal stability and corrosion resistance. Comparative Examples 13-15 (without nano-expansion modifiers): 3h expansion rate dropped to 0.3-0.35%, while 28d shrinkage increased to 0.036-0.040%, demonstrating the critical role of nano-expansion modifiers in volume stability. Comparative Example 16 (without nano-enhancement mixing process): Initial flowability dropped to 278mm, 1d compressive strength was only 49MPa, and total porosity increased to 4.6%, demonstrating the necessity of high-speed shear homogenization for nanoparticle dispersion and interfacial bonding. Synergistic Enhancement Analysis: Functionalized nano-calcium carbonate: Surface modification (silane coupling agent) provides nucleation sites and interfacial reinforcement, significantly improving 1d compressive strength (15-20%) and micro-expansion control (3h expansion rate stabilized at 0.5-1.2%). Energy storage material: paraffin wax and sodium sulfate decahydrate compound provides latent heat ≥ 200 J / g, reduces thermal expansion coefficient (≤ 1.2×10 -6 / °C), enhancing freeze-thaw resistance and durability. Nano-expansion regulators: Magnesium oxide, calcium sulfoaluminate, and nano-graphene oxide synergistically regulate expansion pressure (≤0.5 MPa / day), ensuring a 28-day shrinkage of ≤0.015%. Nano-enhanced mixing process: High-speed shear homogenization (400-500 rpm) breaks down nanoaggregates, achieving a zeta potential ≥30 mV, reducing porosity to ≤2.8%, and improving interfacial bonding strength (Ca-O-Si bond energy ≥530 kJ / mol). Overall synergy: Multi-scale filling (nano-SiO2 / TiO2 / CaCO3 / GO), optimized grading (quartz sand / silica fume / slag powder), and controlled hydration kinetics (CSA rapidly generates AFt, while nano-SiO2 promotes CSH formation) achieve a high-performance grout with a 1-day compressive strength ≥62 MPa and a 28-day shrinkage of ≤0.015%.

[0099] The test results of Examples 1-18 show that by optimizing the proportions and process parameters, the grouting materials have achieved the patented goals in terms of fluidity, early strength, volume stability and durability. Comparative Examples 1-16 verified the necessity and synergistic effect of functionalized nano-calcium carbonate, energy storage materials, nano-expansion regulators and nano-enhanced mixing processes by omitting key components or processes. Functionalized nano-calcium carbonate improves nucleation and interfacial strength, energy storage materials improve thermal stability, nano-expansion regulators ensure micro-expansion without shrinkage, and nano-enhanced mixing processes optimize dispersibility and microstructure, jointly realizing the preparation of high-performance grouting materials suitable for harsh engineering scenarios such as nuclear power containment and large-span bridge bearings.

[0100] The above content is a further detailed description of the present invention in conjunction with specific implementation methods. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, they can make several simple deductions or substitutions without departing from the concept of the present invention, which should be regarded as falling within the scope of protection determined by the claims submitted for the present invention.

Claims

1. A method for preparing an early high-strength, slightly expansive, non-shrinkage grouting material, characterized by: The method comprises the following steps: a. pretreatment of gelled powder: mixing silicate cement, sulfoaluminate cement and nano-silicon dioxide, and then ball milling the mixture at a speed of 500-800 rpm for 60-120 minutes under inert atmosphere to obtain composite gelled powder with a particle size of 0.5-2 μm; b. preparation of dispersed sol: dispersing nano-titanium dioxide, functionalized nano-calcium carbonate and cellulose ether in deionized water under ultrasonic conditions for 30-60 minutes to form a stable dispersed sol; c. preparation of nano-expansion regulating agent: mixing magnesium oxide powder, calcium sulfoaluminate and nano-graphene oxide and deionized water to form a nano-expansion regulating agent; d. preparation of nano-filling system: selecting quartz sand aggregate, silica fume and slag powder, and ball milling and homogenizing the nano-filling system; e. Nano-enhanced mixing process: The composite gelled powder of step a and the nano-filling system of step d are dispersed and mixed in a high-speed disperser at 150-200 rpm for 2-3 minutes, then the nano-swelling regulator of step c is added and the dispersion mixing is continued for 1-2 minutes, and then the dispersed sol of step b is added while increasing the stirring speed to 250-350 rpm and mixing for 5-8 minutes; finally, 5-10 times the mass of the dispersed and dissolved energy storage material is added, and finally a shear homogenization treatment is performed to obtain the product.

2. The method for preparing the early high-strength micro-expansion non-shrinkage grouting material according to claim 1, characterized in that: The mass ratio of silicate cement, sulphoaluminate cement and nano-silicon dioxide in step a is (40-60): (8-15): (0.5-2); the particle size of the nano-silicon dioxide in step a is 10-30 nm.

3. The method for preparing the early high-strength micro-expansion non-shrinkage grouting material according to claim 1, characterized in that: The mass ratio of nano-titanium dioxide, functionalized nano-calcium carbonate, cellulose ether and deionized water in step b is (0.1-0.8): (0.05-0.3): (0.02-0.1): (15-22); the particle size of the nano-titanium dioxide in step b is 5-15 nm; the ultrasonic conditions in step b are as follows: power 200-400 W, frequency 40 kHz.

4. The method for preparing the early high-strength micro-expansion non-shrinkage grouting material according to claim 1, characterized in that: The preparation method of the functionalized nano-calcium carbonate in step b is as follows: a calcium chloride solution with a concentration of 0.5-1.5 mol / L and a sodium carbonate solution with a concentration of 0.5-1.5 mol / L are rapidly mixed at a molar ratio of 1:(2-4) at 20-30° C., the stirring speed is controlled at 300-500 rpm, and the reaction time is 30-60 minutes to generate a nano-calcium carbonate suspension with a particle size controlled at 20-50 nm; 0.05-0.2 times the mass of the nano-calcium carbonate suspension is added to the silane coupling agent KH-570 or KH-550, and the pH value of the solution is adjusted to 8.0-9.

0. Ultrasonic dispersion treatment is performed at a power of 200-400 W and a frequency of 40 kHz for 30-60 minutes to form a modified suspension; The modified suspension is centrifuged to remove unreacted impurities, wherein the centrifugal speed is 5000-8000 rpm and the centrifugal time is 10-20 minutes, washed with deionized water 3-5 times, and then dried in a vacuum drying oven at 60-80° C. for 6-12 hours to obtain functionalized nano-calcium carbonate.

5. The method for preparing the early high-strength micro-expansion non-shrinkage grouting material according to claim 1, characterized in that: In step c, the mass ratio of magnesium oxide powder, calcium sulfoaluminate, nanographene oxide and deionized water is (1.5-4): (0.3-1.2): (0.1-0.5): (6-10).

6. The method for preparing the early high-strength micro-expansion non-shrinkage grouting material according to claim 1, characterized in that: In step d, the mass ratio of quartz sand aggregate, silica fume and slag powder is (100-150): (2-8): (1-5); the parameters of ball milling in step d are as follows: speed 400-500 r / min, time 12-18 h; the parameters of homogenization in step d are as follows: pressure: 40-60 MPa, number of cycles: 3-5 times.

7. The method for preparing the early high-strength micro-expansion non-shrinkage grouting material according to claim 1, characterized in that: In step d, the mass ratio of the composite gelled powder, the dispersed sol, the nano-swelling regulator, and the nano-filling system is (80-100): (8-12): (2-4): (1-2); the parameters of the shear homogenization treatment in step d are as follows: rotation speed 400-500 rpm, time 30-60 s.

8. The method for preparing the early high-strength micro-expansion non-shrinkage grouting material according to claim 1, characterized in that: The preparation method of the energy storage material in step d is as follows: paraffin and sodium sulfate decahydrate with a mass ratio of 1: (3-5) are selected as phase change materials; polymethyl methacrylate is dissolved in acetone 20-40 times its mass to prepare a shell material solution; the phase change material is dispersed in deionized water 30-50 times its mass, and then polyvinyl alcohol 5-10 times the mass of the phase change material is added. Under high-speed stirring at 1200-1500 rpm, 2-3 times the mass of the phase change material is added dropwise to form an oil-in-water emulsion, the temperature is raised to 70-80°C, the reaction is carried out for 4-6 hours to complete the shell polymerization, and then the microcapsules are separated by centrifugation at 8000 rpm for 10 minutes, and the microcapsules are washed alternately with ethanol and deionized water three times, and vacuum dried at 40°C for 24 hours to obtain the energy storage material.

9. An early high strength micro expansion non-shrinkage grouting material, characterized in that: The early high-strength micro-expansion non-shrinkage grouting material is obtained by the preparation method described in any one of claims 1-8.

Citation Information

Patent Citations

  • Electro-optical transducer module

    CA1309484C

  • Machine-made sand light-expansion high early strength grouting material and preparation method thereof

    CN102351492A

  • Environment-friendly phase change microcapsule and preparation method thereof

    CN102838970A

  • Method for preparing calcium carbonate dumbbell-shaped nanoparticles

    CN108101093A

  • Graphene oxide nano-modified cement-based grouting material and preparation method thereof

    CN112341108A

Cited By

  • Coal gangue micro-expansion sealing material as well as preparation method and application thereof

    CN121449388A